Crizotinib-Related Aseptic Abscesses in Lung Adenocarcinoma and ROS1-Gene Rearrangement: A Case Report - Thamires Oliveira-Silva; Camila Naegele-Bazzanella; Mauro Zukin; Nicolle Cavalcante; Antônio Alexandre de-Oliveira-Siciliano; Jaime Araújo-Oliveira-Neto; Clarissa Baldotto (Brazilian Journal of Oncology)
Crizotinib is a multi-tyrosine kinase inhibitor (mTKI) with efficacy in treating c-ROS oncogene 1-positive non-small cell lung cancer (NSCLC). The association between this TKI and the development of renal cysts is well established, although data on the formation of aseptic abscesses is scarce. We report a case of a patient with ROS1-positive NSCLC treated with crizotinib who developed multiple renal and extrarenal cysts and aseptic abscesses associated with a quick resolution of these lesions after the discontinuation of the TKI therapy. We aim to report a rare presentation of a drug-related adverse event with an unusual behavior.